Investigating the driving forces of NOx generation from energy consumption in China. (20th May 2018) - Wang, Junfeng; Qiu, Ye; He, Shutong; Liu, Nan; Xiao, Chengyu; Liu, Lingxuan
Abstract: In China, nitrogen oxide (NOx) emissions have been declining in recent years, whereas NOx generation continues to increase. This has prompted a growing focus of policy design to inspect the driving mechanisms of NOx generation. In this study, a decomposition model of NOx generation in China from 1995 to 2014 was built using the Logarithmic Mean Divisia Index (LMDI) method. According to the decomposition results, technological effects (e.g., energy intensity and the sector generation factor) inhibited NOx generation in China, while gross domestic product (GDP) per capita was found to have the most positive effect on increasing NOx generation, accounting for 151.00% of the total change and showing an increasing trend in recent years. The sector structure of energy consumption always increased NOx generation, which contradicts the results of previous studies. All population effects considered in this study contributed to the growth in NOx generation. The population scale effect was increasingly impactful on the growth of NOx generation; the population spatial structure was active but less impactful. In general, technological impact cannot offset the increases caused by economic, structural, and population effects. Considering NOx reduction policy in China, more attention should be given to emission reduction policies, energy consumption, and socio-economic effects; together, these approaches will improve initiatives to reduce NOx. Graphical abstract: Image 1 Highlights: Temporal, spatial, and structural features on NOx generation in China are shown. Driving forces of NOx generation from energy consumption were studied using LMDI. Energy intensity is the primary factor affecting the reduction of NOx generation. GDP per capita is the primary factor affecting the increase in NOx generation. Population spatial structure has a minor but clear role in increasing NOx generation.